2017
DOI: 10.1111/desc.12569
|View full text |Cite
|
Sign up to set email alerts
|

Lexical‐processing efficiency leverages novel word learning in infants and toddlers

Abstract: Children who rapidly recognize and interpret familiar words typically have accelerated lexical growth, providing indirect evidence that lexical processing efficiency (LPE) is related to word-learning ability. Here we directly tested whether children with better LPE are better able to learn novel words. In Experiment 1, 17- and 30-month-olds were tested on an LPE task and on a simple word-learning task. The 17-month-olds' LPE scores predicted word learning in a regression model, and only those with relatively g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 32 publications
8
35
2
Order By: Relevance
“…For example, by 17 months of age, infants who have better lexical recognition skills are better able to learn novel words in a fairly straightforward task (i.e., when labels are spoken in common ostensive labeling contexts such as "Look, it's a ____") as a single object is presented). By 30 months, LPE no longer predicts word learning in this simple task, but it does when they need to use distributional cues within the sentence to establish reference (Lany, 2017). These findings suggest that LPE may support word learning when it is challenging, and perhaps especially when the words surrounding a novel label provide crucial cues to meaning.…”
Section: Future Directionsmentioning
confidence: 86%
See 3 more Smart Citations
“…For example, by 17 months of age, infants who have better lexical recognition skills are better able to learn novel words in a fairly straightforward task (i.e., when labels are spoken in common ostensive labeling contexts such as "Look, it's a ____") as a single object is presented). By 30 months, LPE no longer predicts word learning in this simple task, but it does when they need to use distributional cues within the sentence to establish reference (Lany, 2017). These findings suggest that LPE may support word learning when it is challenging, and perhaps especially when the words surrounding a novel label provide crucial cues to meaning.…”
Section: Future Directionsmentioning
confidence: 86%
“…At least one study has already begun to ask this question in older infants (Lany, 2017). One way to gain traction in understanding how LPE may support early lexical growth would be to test whether it relates to word-learning processes.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported significant correlations between LWL measures and vocabulary size concurrently in infants (Fernald et al, 2006;Fernald, Marchman, & Weisleder, 2013), and under some conditions this relationship can be observed by as young as 12 months (Lany et al, 2018). Moreover, in some circumstances, infants with comparatively efficient lexical processing learn more words in a word-learning task than those with less efficient lexical processing (Lany, 2018). Retrospectively, individual differences in LWL at 24 months predict size of vocabulary, grammatical complexity, and rate of growth in vocabulary over the first year (Fernald et al, 2006).…”
Section: Introductionmentioning
confidence: 98%